Plant‐phenotypic changes induced by parasitoid ichnoviruses enhance the performance of both unparasitized and parasitized caterpillars. Issue 18 (20th July 2021) - Cusumano, Antonino; Urbach, Serge; Legeai, Fabrice; Ravallec, Marc; Dicke, Marcel; Poelman, Erik H.; Volkoff, Anne‐Nathalie
Abstract: There is increasing awareness that interactions between plants and insects can be mediated by microbial symbionts. Nonetheless, evidence showing that symbionts associated with organisms beyond the second trophic level affect plant‐insect interactions are restricted to a few cases belonging to parasitoid‐associated bracoviruses. Insect parasitoids harbour a wide array of symbionts which, like bracoviruses, can be injected into their herbivorous hosts to manipulate their physiology and behaviour. Yet, the function of these symbionts in plant‐based trophic webs remains largely overlooked. Here, we provide the first evidence of a parasitoid‐associated symbiont belonging to the group of ichnoviruses which affects the strength of plant‐insect interactions. A comparative proteomic analysis shows that, upon parasitoid injection of calyx fluid containing ichnovirus particles, the composition of salivary glands of caterpillars changes both qualitatively (presence of two viral‐encoded proteins) and quantitatively (abundance of several caterpillar‐resident enzymes, including elicitors such as glucose oxidase). In turn, plant phenotypic changes triggered by the altered composition of caterpillar oral secretions affect the performance of herbivores. Ichnovirus manipulation of plant responses to herbivory leads to benefits for their parasitoid partners in terms of reduced developmental time within the parasitized caterpillar. Interestingly, plant‐mediated ichnovirus‐induced effects also enhance the performances of unparasitized herbivores which in natural conditions may feed alongside parasitized ones. We discuss these findings in the context of ecological costs imposed to the plant by the viral symbiont of the parasitoid. Our results provide intriguing novel findings about the role played by carnivore‐associated symbionts on plant‐insect‐parasitoid systems and underline the importance of placing mutualistic associations in an ecological perspective.